THE NURSING CARE TO THE CRITICAL PATIENT IN FAMILY'S PERCEPTION - Rúbia Manetti Mezzaroba; Vívian Maria de Freitas; Kátia Renata Antunes Kochla (Universidade Federal do Paraná, 2009)
Descriptive-exploratory study, performed in a Semi-intensive Therapy Center (CTSI) in a large Public UniversityHospital in Curitiba. The objectives were to understand the meaning of nursing care to the critical patient's relatives andto identify if the nursing team meets family's expectations. The study's subjects were relatives of patients who werehospitalized in February 2008. Data survey was performed through interviews and organized in categories. For the subjects,nursing care is related to technical actions and to the attention the team dedicates to patient. Families consider that if theteam takes care with love and tenderness, the results will be positive to patient recovery. A significant part of interviewedpeople indicated that their expectations were met and another part considered nursing team contacts were unsatisfactory.This study showed the necessity of a nursing team reflection on the importance of family's perception regarding care.